Efektivitas Aplikasi Info BMKG dalam Memberikan Informasi Cuaca dan Bencana - Andi Prasetiyo (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The Info BMKG application is a digital platform developed by the Meteorology, Climatology, and Geophysics Agency (BMKG) to provide information on weather, earthquakes, air quality, and early disaster warnings. This application is expected to enhance public preparedness in facing potential natural disasters. However, in its implementation, the Info BMKG application still encounters several issues, one of which is delays in delivering weather and disaster information. This study aims to analyze the effectiveness of the Info BMKG application in providing weather and disaster information. The research applies Budiani's (2007) theory, using four indicators: Program Target Accuracy, Program Socialization, Program Objectives, and Program Monitoring. This study employs a qualitative descriptive method with data collection through interviews, observations, and documentation. The findings indicate that the Info BMKG application has made a significant contribution to supporting public preparedness for disasters. While the application is relatively effective in providing weather and disaster information in North Jakarta, further development is still needed. Improvements in information accuracy, notification speed, and enhanced public socialization will help improve the quality of the application’s services in the future.